China’s Belt and Road Initiative and its role in global poverty reduction - Arif, Muhammad Nur; Loong, Yung Yik; Nizam, Khairul; Yasin, Yusma Fariza; Yusof, Junaidah (Journal of Islamic, Social, Economics and Development, 2025)
The Belt and Road Initiative (BRI), launched by China in 2013, is one of the most ambitious global development frameworks of the 21st century. Encompassing the Silk Road Economic Belt and the 21st-century Maritime Silk Road, the initiative seeks to enhance regional integration through large-scale investments in infrastructure, trade, finance, and cultural exchange across Asia, Europe, Africa, and beyond. While the BRI has mobilized unprecedented financial resources and expanded connectivity to more than 140 countries, it has also raised concerns over debt sustainability, governance challenges, and the growing dependence of participating nations on China. These issues have generated debate over whether the initiative is a genuine development strategy or a geopolitical instrument that prioritizes China’s strategic interests. This study adopts a qualitative approach through critical review and synthesis of existing literature, policy reports, and secondary data. The analysis focuses on the BRI’s structural pillars, economic potential, and emerging challenges, particularly its implications for poverty reduction and sustainable development. Findings indicate that the BRI plays a dual role as both a driver of development and an instrument of geopolitical influence. While infrastructure development has created new opportunities for trade and connectivity, debt risks, transparency, and environmental sustainability challenges persist. Moreover, the initiative’s long-term impact varies significantly across participating countries, depending on governance capacity and policy alignment. The study recommends the development of a more transparent, inclusive, and sustainable BRI framework that emphasizes equitable partnerships, debt management strategies, and environmentally responsible investments. Strengthening multilateral cooperation and embedding robust governance mechanisms will ensure that the BRI contributes meaningfully to global poverty reduction and long-term development goals.